A study of the styles of leadership in a small service industry: A qualitative case study of Wira Ukur Consultant, Kota Bharu, Kelantan, Malaysia - Hanafi Mamat (2023)
This research was performed to identify the perception and understanding of leadership by the top management, middle management and the non- managerial employees. Secondly, to identify the types of leadership styles adopted by the management in a small service industry in the state of Kelantan Malaysia. Thirdly, to discover how could the styles of leadership can contribute to the sustainability of the business for 30 over years. The case study was done on a single company Wira UKUR Consultant. The researcher was of the opinion the findings will represent other firms of the same size and industry. Literature review was done on several styles of leadership namely, Ethical leadership styles, Entrepreneurial, Transformational, Transactional, Coaching, Islamic and other leadership styles that researchers has studied. The methodology employed for data collection in this research is in the form of individual interviews, focus group discussion and company’s record. The questions are a combination of structured, semi structured, unstructured and a combination of impromptu dialog to gain the understanding and to get the question across so as to ensure the respondents answered them correctly as what was asked. The research also dealt with the present state of performance of the company. The findings point to three dominant styles of leadership. It was revealed by the respondents’ answers that the styles adopted, are coaching, Islamic and ethical. Other styles existed too but of no significant dominance. Coaching leadership deals with optimism, self-efficacy, positive emotions and learning. The aim is achieving personal and organisational goals. Ethical leadership deals with integrity and upholding high moral ground and avoid negative characters such as taking advantage to gain from other people’s predicament. While Islamic leadership styles conform to religious obligation doing positive deeds and avoiding deeds despised by society. The sustainability of this company for thirty over years is the results of these leadership styles adopted. These styles have given confidence to the employees and they trust the company and there is low incidence of turnover. They remain in company until retirement. The customers remain loyal and as a result there were continuous stream of jobs for the company. Wira ukur consultant has become a trusted brand in Land Surveying Service industry.